Storm-time variations of atomic nitrogen 149.3 nm emission. (April 2018) - Zhang, Y.; Paxton, L.J.; Morrison, D.; Schaefer, B.
Abstract: Net radiances of atomic nitrogen emission line (N-149.3 nm) from the thermosphere are extracted from the FUV spectra observed by TIMED/GUVI on dayside at sunlit latitudes. During geomagnetic storms, the N-149.3 nm intensity is clearly enhanced in the locations where O/N2 depletion and nitric oxide (NO) enhancement are observed. The N-149.3 nm intensity is linearly and tightly correlated with N2 LBHS (140–150 nm) radiance with a fixed LBHS/149.3 nm ratio of ∼4.5, suggesting that dissociation of N2 is the dominant source of the N-149.3 nm emission. In the regions without storm disturbances, the N-149.3 nm intensities are closely correlated with solar EUV flux. Highlights: A new algorithm is developed to extract the dayside net radiances at 149.3 nm from atomic nitrogen. Anti-correlation between global thermospheric O/N2 ratio and N-149.3 nm. Storm-time enhancements in N-149.3 radiance indicate the N2 density enhancement in the thermosphere. Non-storm time variations in N-149.3 are controlled by solar EUV flux.